2022
DOI: 10.3390/rs14061301
|View full text |Cite
|
Sign up to set email alerts
|

Time-Lag Effect of Vegetation Response to Volumetric Soil Water Content: A Case Study of Guangdong Province, Southern China

Abstract: The content of soil water affects the physiological activities of vegetation, and the type of vegetation also affects the soil water balance. It is of great significance to study the response of vegetation to soil moisture change, which is helpful for understanding the vulnerability of vegetation for regional and environmental protections. The response of vegetation to soil moisture in Guangdong Province from mid-October 2015 to the end of March 2017 was studied by using cloudy region drought index (CRDI) as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Under controlled irrigation, Liu et al (2018) found that SIF and indices calculated at wavelengths between 680 nm and 750 nm are related to soil moisture at different depths and exhibit different response times on wheat. Therefore, it should be noted that the responses of spectral indices to soil water profile and response times depend on the climatic regimes of the study area, the type of vegetation and its phenological stage, the depth and distribution of the roots, the soil physical characteristics and the spatial scale of the observation (Celik et al 2022;Li et al 2022;Liu et al 2018;Pablos et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Under controlled irrigation, Liu et al (2018) found that SIF and indices calculated at wavelengths between 680 nm and 750 nm are related to soil moisture at different depths and exhibit different response times on wheat. Therefore, it should be noted that the responses of spectral indices to soil water profile and response times depend on the climatic regimes of the study area, the type of vegetation and its phenological stage, the depth and distribution of the roots, the soil physical characteristics and the spatial scale of the observation (Celik et al 2022;Li et al 2022;Liu et al 2018;Pablos et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The time lag effect is a key characteristic in the interaction between SM and vegetation. This means local SM (vegetation) may have a closer connection with temporarily lagging vegetation (SM) [7,13]. Li et al [14] concluded that moist soil can promote sequential vegetation growth.…”
Section: Introductionmentioning
confidence: 99%
“…The soil moisture content within the root zone (0-15 cm) exerts a profound influence on crop physiological states. Theoretically, it can be indirectly assessed through the analysis of crop canopy reflectance or vegetation indices [14,15]. The relationship between soil moisture content and vegetation spectra is intricate, posing challenges for classical regression methods in achieving unbiased and effective parameter estimation [16,17].…”
Section: Introductionmentioning
confidence: 99%